Hierarchically structured, Janus optical nanoengineered wastepaper for switchable radiative cooling/heating - Zifan Song; Zipeng Zhang; Xueting Zhang; Jingyang Liu; Wanjie Wang; Jianfeng Wang; Xiuxiu Jin (Carbon Energy)
Abstract Switchable radiative cooling/heating holds great promise for mitigating the global energy and environmental crisis. Here, we reported a cost‐effective, high‐strength Janus film through surface optical engineering waste paper with one side decorated by a hydrophobic polymeric cooling coating consisting of micro/nanopore/particle hierarchical structure and the other side coated with hydrophilic MXene nanosheets for heating. The cooling surface demonstrates high solar reflectivity (96.3%) and infrared emissivity (95.5%), resulting in daytime/nighttime sub‐ambient radiative cooling of 6°C/8°C with the theoretical cooling power of 100.6 and 138.5 W m−2, respectively. The heating surface exhibits high solar absorptivity (83.7%) and low infrared emissivity (15.2%), resulting in excellent radiative heating capacity for vehicle charging pile (~6.2°C) and solar heating performance. Impressively, the mechanical strength of Janus film increased greatly by 563% compared with that of pristine waste paper, which is helpful for its practical applications in various scenarios for switchable radiative thermal management through mechanical flipping. Energy‐saving simulation results reveal that significant total energy savings of up to 32.4 MJ m−2 can be achieved annually (corresponding to the 12.4% saving ratio), showing the immense importance of reducing carbon footprint and promoting carbon neutrality.